2014
DOI: 10.1353/pla.2014.0006
|View full text |Cite
|
Sign up to set email alerts
|

Resilience and Redirection: Information Literacy in Louisiana Higher Education

Abstract: This article reports on a 2012 survey conducted by members of the Louisiana Academic Library and Information Network Consortium (LALINC) to determine the status of the curricular integration of information literacy instruction following numerous budget cuts to Louisiana higher education since 2008. The article also discusses the 2012 deletion of the information literacy requirement from the Louisiana Board of Regents’ general education requirements and provides a comparison of general education and library req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…18 Jessica Hutchings and Malia Willey surveyed 47 colleges and universities in Louisiana in 2014 and found that credit-based IL course offerings are at 32 percent. 19 Otis Chadley and Jacquelyn Gavryck looked at 72 ARL libraries in 1989 and reported that 33 percent of them offer credit-based IL courses. 20 The literature offers a rich picture of prevalence of credit-bearing IL efforts that are underway at U.S. academic libraries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…18 Jessica Hutchings and Malia Willey surveyed 47 colleges and universities in Louisiana in 2014 and found that credit-based IL course offerings are at 32 percent. 19 Otis Chadley and Jacquelyn Gavryck looked at 72 ARL libraries in 1989 and reported that 33 percent of them offer credit-based IL courses. 20 The literature offers a rich picture of prevalence of credit-bearing IL efforts that are underway at U.S. academic libraries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[18][19][20] Indeed, the importance of information literacy as a subset of skills need for lifelong learning was emphasised as being of prime importance by a number of workers over many years. 1,13,21,22 Referencing strategies that engineering students use 'to synthesise and cite information from sources in composing their literature review' was considered to be of vital importance to engineers. 23 Producing an information-literate student who is knowledgeable about finding, retrieving, analysing, and effectively using information is a common goal amongst librarians.…”
Section: Introductionmentioning
confidence: 99%